PET/CT appearance of desmoid tumour of the chest wall - Souza, F F (The British Institute of Radiology., 2010)
Desmoid tumours are rare, poorly circumscribed tumours that have a firm consistency and, although benign, have a remarkable tendency to infiltrate into surrounding structures. Extra-abdominal desmoid tumours involve mainly the extremities or the chest wall and are usually managed by wide radical resection. Moreover, desmoid tumours involving the chest wall are locally aggressive tumours with a high recurrence rate. We report a case of a pathologically proven desmoid tumour of the chest wall in a patient with a history of bilateral breast cancer and oesophageal cancer. We discuss the imaging appearances of this tumour on positron emission tomography combined with computed tomography (PET/CT) and magnetic resonance imaging.